The Effect of Corporate Social Responsibility (CSR) Disclosure on Earnings Quality - Taufikurachman, Cecep; Harto, Budi; Napisah, Lilis Saidah (Fakultas Ekonomi Universitas Garut, 2023)
Financial reports provide crucial data for decision-making processes. An increase in corporate profits is possible if more emphasis is placed on CSR. The purpose of this study is to learn how CSR reporting influences the quality of companies listed on IDX between 2017 and 2021. This study employed both descriptive and confirmatory research methods. This study focuses on the population of hotels, restaurants, and travel agencies that are registered in IDX from 2017 to 2021.